THE NOTION OF HUMAN FREEDOM AND ITS IMPLICATION IN OUR SOCIETY TODAY - Ephraim, U Ibekwe (PEOPLE: International Journal of Social Sciences, 2020)
A major problematic concept in our world today is that of freedom which has gained prominence into mainstream discussions. Everyone craves freedom, since “it is only in freedom that man realizes his being” yet only a few think about the responsibilities of freedom. Here we encounter the problems inherent in the possibility of human free choice of actions as preordained by forces beyond his control and opposed to his will, the reconciliation of our answers to human freedom with our acknowledgment of objective necessity, and whether humans are not means of realizing the laws of social development. These and many more puzzles point to the fact that the problem of freedom has remained a perennial one down the ages. Freedom is a distinctive quality of man from other beings. A man beyond being intelligent is also free in his actions and deliberations in the face of decisions and choices. This article hence takes a critical look at the concept of Freedom. Adopting a critical methodological outlook from Satrean dimension, it exposes its nature and pays particular attention to its attendant consequences in our society today.